Teaching methodologies in the scope of collaborative design towards cultural interaction - Rijo, Cátia (2019)
The aim of this paper is to present a reflection about the importance of collaborative work between students in different cultures and context realities, using as a launch method, a design thinking workshop. The goals of the workshop were, by introducing the principles of design thinking to a focus group of university students, in Finland and Portugal, to implement and develop, the ability to experiment the design thinking process, and to realize how the interaction of different perspectives, can lead to innovative solutions, as to the promotion of interdisciplinary work. Design Thinking is a flexible methodology, that can be used in any work field, since it as valuable elements, such as iterating frequently based on continuous feedback from all the intervenient. During the workshop, the teams followed the stages of the interactive Design Thinking Microcycle: (re)Defining the problem, Need finding and Benchmarking, Ideation, Prototyping and Testing. This approach leads to a high variety of ideas. Through rapid low-resolution prototyping ideas are continuously being tested with the potential users. “Fail early in order to succeed sooner” is the Design Thinking principle that helps to maximize learnings and insights, crucial for human centered innovation. Collaborative work in a small groups scenario map, leads to the discussion of solutions, and to the innovation that emerges from the different perspectives given by each person. Our main goal, was to find business opportunities that emerge from underestimated issues from everyday life, but also to understand that exploring, understanding, and prioritizing areas, can be crucial to ideating solutions. As final result we intend to analyze and compare results from each focus group, in Finland and in Portugal, in order to understand the differences to the problem solving approach, from each cultural and social context.